Methodology of Forming Professional Qualities of Students - Urinov Uygun Abdullayevich; Abdullayeva Nigina Khamidovna (European Science Publishing, 2023)
This article talks about the formation of professional qualities of students in the educational system. Ways to arouse students ' interest in science and increase their activity are presented. Features of the use of advanced pedagogical technologies in educational institutions for imparting knowledge, skills and qualifications to students are described.
Keywords: professional quality, lesson, student, educational system, knowledge, skill, competence, interest.